ELT in Literature: Using Poetry in Enhancing Students Speaking Performance - Agung Suhadi (English Teaching and Linguistics Journal (ETLiJ), 2023)
ELT in literature is one form of teaching integration, which is considered effective way for learner motivation, and a positive atmosphere in learning language. This research presents the study of teaching integration by using poetry as a medium for enhancing students speaking performance. This aims to analyze how the students' performance in English speaking by using poem in literature. The qualitative descriptive method is employed towards research samples from 15 groups students at the Prose and Poetry coursework. Data collection techniques were taken by observing closely towards students' conversation activities by using poetry, which are further analyzed by using Hughes' speaking rubrics, such as fluency, details or understanding, vocabulary, grammar, and pronunciation. The results obtained that the use of poetry as a medium for conversation activity impacts on students' speaking performance, particularly vocabulary, pronunciation, and fluency. In short, this finding is a very interesting way, which can be widely offered in ELT program, such as basic English.